2018
DOI: 10.1016/j.neuroimage.2017.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of spoken and written language processing in the superior temporal sulcus

Abstract: Spoken and written language processing streams converge in the superior temporal sulcus (STS), but the functional and anatomical nature of this convergence is not clear. We used functional MRI to quantify neural responses to spoken and written language, along with unintelligible stimuli in each modality, and employed several strategies to segregate activations on the dorsal and ventral banks of the STS. We found that intelligible and unintelligible inputs in both modalities activated the dorsal bank of the STS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 115 publications
7
63
0
Order By: Relevance
“…Peak regions of activation also were found in the MTG, extending to temporooccipital cortex. Like the STG, this region has been implicated in lexical processing (Hickok & Poeppel, , , ; Hagoort, ; see Lau, Phillips, & Poeppel, for review) and has been shown in previous neuroimaging studies to be responsive to both visual and auditory sentence structural manipulations (Wilson, Bautista, & McCarron, ). A recent study using electrocorticography (ECoG) (Nelson et al, ) also suggests that the posterior MTG is associated with predictive (top‐down) processing, which is engaged for sentence comprehension in healthy listeners (Lau, Stroud, Plesch, & Phillips, ; Mack, Ji, & Thompson, ; and others).…”
Section: Discussionmentioning
confidence: 99%
“…Peak regions of activation also were found in the MTG, extending to temporooccipital cortex. Like the STG, this region has been implicated in lexical processing (Hickok & Poeppel, , , ; Hagoort, ; see Lau, Phillips, & Poeppel, for review) and has been shown in previous neuroimaging studies to be responsive to both visual and auditory sentence structural manipulations (Wilson, Bautista, & McCarron, ). A recent study using electrocorticography (ECoG) (Nelson et al, ) also suggests that the posterior MTG is associated with predictive (top‐down) processing, which is engaged for sentence comprehension in healthy listeners (Lau, Stroud, Plesch, & Phillips, ; Mack, Ji, & Thompson, ; and others).…”
Section: Discussionmentioning
confidence: 99%
“…Networks for speech perception strongly implicate mid-to-posterior superior temporal gyrus (STG) regions extending roughly from the lateral aspect of the gyrus into the dorsal bank of the superior temporal sulcus (STS) (Hickok & Poeppel, 2007). (See Wilson et al, 2018a for evidence that the dorsal and ventral banks of the posterior STS are functionally distinguishable).…”
Section: Syntax 14mentioning
confidence: 99%
“…Future research using a similar experimental design should explore other modalities of presentation, such as auditory speech and sign language. Previous studies using these disparate modalities have illustrated similar effects with tight overlap in the pSTS/MTG and Broca's area (MacSweeney 2002;MacSweeney et al 2006;Spitsyna et al 2006;Jobard et al 2007;Lindenberg and Scheef 2007;Pa et al 2008;Berl et al 2010;Leonard et al 2012;Vagharchakian et al 2012;Regev et al 2013;Wilson et al 2018). Therefore we would expect the same production-perception asymmetry across modalities in these regions.…”
Section: Discussionmentioning
confidence: 74%